Integrating Artificial Intelligence and Advanced Genomic Technologies in Unraveling Autism Spectrum Disorder and Gastrointestinal Comorbidities: A Multidisciplinary Approach to Precision Medicine - Ghunaim, Lama; Ali Agha, Ahmed Saad Abdulbari; Aburjai, Talal (Jordan Journal of Pharmaceutical Sciences, 2024)
This article explores the potential impact of Artificial Intelligence (AI), Machine Learning (ML), CRISPR-Cas9 gene editing, and single-cell RNA sequencing on improving our understanding and management of Autism Spectrum Disorder (ASD) and its gastrointestinal (GI) comorbidities. It examines how these technologies illuminate the complex interplay between the gut and the brain, identifying specific enzyme deficiencies and microbial imbalances linked to GI symptoms in ASD. By leveraging AI and ML, personalized intervention strategies are developed through the analysis of genomic, proteomic, and environmental data, enhancing our ability to predict and address GI issues in ASD. Additionally, CRISPR-Cas9 gene editing holds promise for correcting genetic abnormalities related to enzyme production, potentially offering precise treatments. Single-cell RNA sequencing provides critical insights into the cellular diversity of the ASD gut, uncovering new therapeutic targets. The article highlights the transformative potential of these technologies while addressing the associated challenges and ethical considerations. It underscores the necessity of a multidisciplinary approach to fully harness their benefits and discusses the significant progress and emerging trends in the field, emphasizing the role of technological advancements in advancing precision medicine for ASD and its GI comorbidities.